Mutual Savings Banks in the Savings and Mortgage Market (Book). - Tracy, Truman G.; Bray, Robert E. (The Accounting Review, 1949)
Abstract Reviews the book "Mutual Savings Banks in the Savings and Mortgage Market," John Lintner.